Methodological aspects of the organization of research works on geometry for basic school students based on the Technopark of Universal Pedagogical Competencies - Trushnikova K. V., Smykovskaia T. K. (Technopark of universal pedagogical competencies, 2024)
The article raises the problem of organizing research work on geometry for students of the basic school on the basis of the Technopark of universal pedagogical competencies. A set of tasks is considered that ensure the organization of research work using the resources and equipment of the Technopark.
Keywords: исследовательские задания; методика обучения; teaching methods; технопарк; Technopark; исследовательская работа; обучение геометрии; research work; geometry training